(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This paper presents a conceptual discussion that integrates the concept of behavioral cusp to the Social Skills field. A Behavioral Cusp implies a behavioral change that provides the access to new contingencies, new ambient, controlling variables and social groups. There are evidences highlighting the relationship between behavioral problems and lack of social skills in adolescents. Several studies indicate that the quality of interactions with peers is affected by a broad repertoire of social skills, which in turn indicates the criteria of the access to new ambient (behavioral cusp). It is assumed that the development of a repertoire of social skill compete with problem behaviors, for example antisocial behavior and drug abuse, emphasizing a behavioral cusp characteristic. In sum, the advantages of interpreting social skills as behavioral cusp rely on planning effective behavioral interventions.